Nothing Absolute German Idealism and the Question of Political Theology - Albernaz, Joseph; Barber, Daniel Colucciello; Bielik-Robson, Agata; Chepurin, Kirill; Chrostowska, S. D. 1975-; Das, Saitya Brata ca. 20./21. Jh; Dubilet, Alex ca. 20. Jh; Lynch, Thomas 1982-; Martel, James R. (Perspectives in Continental Philosophy, 2021)
Featuring scholars at the forefront of contemporary political theology and the study of German Idealism, Nothing Absolute explores the intersection of these two flourishing fields. Against traditional approaches that view German Idealism as a secularizing movement, this volume revisits it as the first fundamentally philosophical articulation of the political-theological problematic in the aftermath of the Enlightenment and the advent of secularity.Nothing Absolute reclaims German Idealism as a political-theological trajectory. Across the volume's contributions, German thought from Kant to Marx emerges as crucial for the genealogy of political theology and for the ongoing reassessment of modernity and the secular. By investigating anew such concepts as immanence, utopia, sovereignty, theodicy, the Earth, and the world, as well as the concept of political theology itself, this volume not only rethinks German Idealism and its aftermath from a political-theological perspective but also demonstrates what can be done with (or against) German Idealism using the conceptual resources of political theology today.Contributors: Joseph Albernaz, Daniel Colucciello Barber, Agata Bielik-Robson, Kirill Chepurin, S. D. Chrostowska, Saitya Brata Das, Alex Dubilet, Vincent Lloyd, Thomas Lynch, James Martel, Steven Shakespeare, Oxana Timofeeva, Daniel Whistler